Aqueous MW eco-friendly protocol for amino group protection1. Issue 24 (15th March 2015) - Nardi, M.; Cano, N. Herrera; Costanzo, P.; Oliverio, M.; Sindona, G.; Procopio, A.
<x xml:space="preserve">Abstract</x> In this paper a new catalyst-free and on-water method for protection of amines and amino acids with di-tert-butyl dicarbonate, 9-fluorenylmethoxycarbonyl chloride, acetyl chloride and tosyl chloride is presented.